2009
DOI: 10.1007/s11661-009-0106-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Start Curves of Bainite Formation

Abstract: It is demonstrated that calculations with a physically based model give an accurate description of the start curve of bainite formation in a wide range of steels. The temperature dependence of the overall kinetics, which determines the characteristic C shape of the start curve, is controlled by both the undercooling below the start temperature (T h À T) and an effective activation energy Q b . A systematic analysis of the model parameters extracted from the best fits of published time-temperature-transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
2
37
1
Order By: Relevance
“…All the details about the sample preparation can be found in these prior papers. The Ms value of the studied steel, 295 • C, was measured during the in situ investigations, and was consistent with the value calculated with the model developed by Van Bohemen (298 • C) [25,26].…”
Section: Studied Alloysupporting
confidence: 88%
See 1 more Smart Citation
“…All the details about the sample preparation can be found in these prior papers. The Ms value of the studied steel, 295 • C, was measured during the in situ investigations, and was consistent with the value calculated with the model developed by Van Bohemen (298 • C) [25,26].…”
Section: Studied Alloysupporting
confidence: 88%
“…For the investigated alloy, the predicted retained austenite fraction as a function of the QT after the long partitioning time is represented in Figure 2. The calculation relied on a Carbon Constraint Equilibrium (CCE) assumption and the empirical Van Bohemen et al [25,26] equations for martensitic transformations (initial and final). The CCE is an interface condition between martensite and austenite assuming that only the chemical potential of carbon must be equilibrated in both phases, and that the interface is fixed as a consequence [4][5][6].…”
Section: Quenching and Partitioning (Qandp) Processing Conditionsmentioning
confidence: 99%
“…In the case of high-Si steels, when the carbon concentration of the austenite increases, j will decrease due to a higher effective activation energy Q b and a smaller undercooling (T h -T) [9]. Furthermore, the above equations show that the kinetics are inversely proportional to the austenite grain diameter d c [8,12] because the austenite grain boundaries provide the nucleation sites initially present.…”
Section: Theorymentioning
confidence: 97%
“…[8] the constants d and Z, respectively the effective thickness of the austenite grain boundary and a geometrical factor, are chosen as d = 1 nm and Z = 6. The parameter K 1 is a material constant [9], and C =d(DG m )/dT is the derivative of the maximum driving force DG m with respect to T. The autocatalytic parameter k can be determined on the basis of isothermal fraction-time curves [3,8]. It has been found that k increases with increasing austenite grain size d c [8] and some studies suggest that k might also be dependent on the chemical composition [3,17].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation